Planning, training, and skills assessment in lifelong learning for adult workers - Daniela Robasto (Firenze University Press, 2019)
The school system has customarily emphasized a difference between an educational context designed to expand knowledge, and a professional context necessarily focusing on situated competence. This double antithesis of a) knowledge vs. competence and b) school vs. work has led and is always likely to lead to substantial misconceptions with harmful repercussions. Firstly, that inserting a professional context in a school context inexorably leads to skills building. Secondly, the misconception, discussed here, that in lifelong learning, training and assessment have been carried out for some time with an eye on competence. This study examines the recent regulations on the training and certification of skills in formal, informal and non-formal contexts and the guidelines of the main inter-professional funds, which reveal that planning and assessment in lifelong learning in terms of competence, are recent requests, which are triggering the same resistance and critical concerns already seen and experienced in scholastic contexts. Progettare, formare e valutare per competenze nella formazione continua dei lavoratori in servizio Non raramente nel mondo dell'istruzione si è vista delineata una doppia e intrecciata antitesi a) conoscenza vs. competenza + b) scuola vs. lavoro. L'antitesi poggia su misconcezioni notevoli, dalle ricadute potenti, in primis quella che innestare il contesto professionale nel contesto scolastico conduca ineluttabilmente alla costruzione di competenze; in secondo luogo, la misconcezione, qui affrontata, secondo la quale nella formazione continua da tempo si progetti, si formi e si valuti per competenze. Dopo un'analisi internazionale volta ad individuare il profilo tipo del destinatario della formazione continua in Italia, il presente studio esplorativo prende in esame i recenti riferimenti normativi relativi alla formazione e certificazione delle competenze dei contesti informali e non formali e le linee guida dei principali fondi interprofessionali, documentando piuttosto quanto la progettazione e valutazione per competenze, nell'ambito della formazione continua, siano richieste recenti, che stanno innescando le note criticità progettuali già esperite nei contesti scolastici.